Explorando funcionalidades sociais e colaborativas em ambientes educacionais ubíquos - Mendonça, Igor Emmanuel Silva (2015)
Research and projects that exploit the ubiquitous computing paradigm in the education domain are recurrent in the literature, opening the way for the development and experimentation with new forms of communication, collaboration and organization of information. In this context, this work presents a software architecture model that supports collaborative activities for extension and enrichment of digital content through annotation and classication (ranking) in ubiquitous educational environments. The proposed model uses concepts of hypermedia composition and is capable of generating subsidies to meet recommendation requirements and customization of multimedia digital content. As a proof of concept, a Web application was built to allow the creation of comments and ratings over multimedia digital content. For validating the proposal, such application was integrated to the Classroom eXperience platform as an additional module, and its use by groups of undergraduate courses at Federal University of Uberlândia was assisted over two semesters. In the validation approach, it was applied an adaptation of the Technology Acceptance Model, in order to determine the receptivity and the impact of the inclusion of new features by students using the platform. As a result, it was found that the collaborative module has been well received by users and contribute to the attractiveness of the platform, increasing its levels of access. It was also observed that such incentive to use the system also contributed to the nal performance of the students, showing that approaches that aim at providing interactive features in a virtual environment and encouraging collaborative learning have great potential for the development of teaching and learning processes in the educational eld.